Sufficient Condition for the Property of a Graph to be Bipartite - Kamalian, Rafael R.; Mkrtchyan, Vahagn V. (Mathematical Problems of Computer Science, 2024)
A sufficient condition is found to determine when a graph with vertices on the integer sieve of Rn is bipartite. This condition can be useful in cases when the description of a graph does not contain an appropriate bipartition of the set of its vertices.